Here's the question you clicked on:
Torrayani<3
If f(x) = x + 3 and g(x) = −4x − 1, find g[f(4)]
for these problems, if you haven't caught on yet you have to plug the 4 into the question of f then into the equation of g \[f(4)=4+3=7, g(f(4))=-7(4)-1=-29\]
f(x) = x + 3 g(x) = −4x − 1 g(f(x)) = -4(f(x)) - 1 = -4(x + 3) - 1 = -4x - 12 - 1 = -4x - 13 g(f(4)) = -4(4) - 13 = -16 - 13 = ?
marvin gimme my medal back!!
you have to plug four into f and u get seven and then plug 7 into g
For these problems, find g(f(x)) first. Then plug in x = 4 to get g(f(4))
@zachy1234, You giving answers is what's not helping at all.
thank you everyone since i can't give medals to all I'll just fan every1
@Hero can you explain more